Prolonged occupational exposure leads to allergic airway sensitization and chronic airway and systemic inflammation in professional firefighters. (September 2016) - Gianniou, Niki; Katsaounou, Paraskevi; Dima, Efrossini; Giannakopoulou, Chariklia-Eleni; Kardara, Matina; Saltagianni, Vassiliki; Trigidou, Rodoula; Kokkini, Aggeliki; Bakakos, Petros; Markozannes, Evangelos; Litsiou, Eleni; Tsakatikas, Alexandros; et al.
Abstract: Background and objectives: Little data exist on short- and long-term effects of occupational exposure on airway and systemic inflammation in professional firefighters. We aimed to characterize airway and systemic inflammation in training firefighters with a maximum occupational exposure of 1 year compared to the long-term exposure of professional firefighters. Methods: A questionnaire for symptoms and exposure, pulmonary function, atopy, bronchial hyper-responsiveness, and markers of inflammation in induced sputum, serum, bronchoalveolar lavage (BAL) fluid and bronchial biopsies were assessed in a total of 92 firefighters (63 full-time professionals and 29 trainees). Results: Professional firefighters showed allergic bronchial sensitization documented by the presence of atopy, and eosinophilia in induced sputum, BAL and bronchial biopsies. IL-8, ECP, VEGF, and TNF-α levels were statistically significantly higher in the sputum supernatants of professional firefighters compared to the trainees (p = 0.04, p = 0.02, p = 0.04, and p = 0.02, respectively). Serum IL-8 and TNF-α levels were also statistically significantly higher in the group of professional firefighters (p = 0.04, p = 0.03, respectively). Finally, there was a linear correlation between the duration of the occupation in Service and the degree of airway and systemic inflammation. Conclusions: These results indicate a "dose-response" effect of chronic exposure to a polluted environment on bronchial and systemic inflammation in professional firefighters. Highlights: Prolonged exposure to smoke induces a local inflammatory response within the lungs, which initiates a systemic response. Chronic exposure to air pollutants and combustion products may lead to increased sensitization to airway allergens. Awareness should be heightened among firefighters to adequately use the self-contained breathing apparatuses during operations.